1987
DOI: 10.1152/jappl.1987.62.4.1398
|View full text |Cite
|
Sign up to set email alerts
|

Micropolyspora faeni causes airway inflammation but not hyperresponsiveness in sensitized ponies

Abstract: We assessed the effect of aerosol Micropolyspora faeni challenge in two groups of ponies by measuring lung function, airway reactivity to aerosol histamine, and bronchoalveolar lavage fluid cytology. One group of ponies was sensitized by subcutaneous injection of M. faeni in complete Freund's adjuvant, and the other group served as control. In both groups of ponies, measurements were made at base line and 5 h after aerosol administration of 30 ml of saline or 30 ml of 1% wt/vol particulate M. faeni antigen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…Results of the study also revealed that neutrophilic inflammation of the respiratory tract' s smaller airways may be observed in horses that do not have COPD and that airway inflammation is not necessarily associated with lung dysfunction. These findings are in agreement with studies in which investigators observed an influx of neutrophils in airways of equids exposed to molds 4,37,45 ; however, only equids with COPD had changes in lung function. We speculate that when the inflammatory process is sufficient in duration or severity, changes in morphologic characteristics of the airways will develop, leading to impairment of lung function, such as has been proposed in humans with asthma.…”
Section: Discussionsupporting
confidence: 92%
“…Results of the study also revealed that neutrophilic inflammation of the respiratory tract' s smaller airways may be observed in horses that do not have COPD and that airway inflammation is not necessarily associated with lung dysfunction. These findings are in agreement with studies in which investigators observed an influx of neutrophils in airways of equids exposed to molds 4,37,45 ; however, only equids with COPD had changes in lung function. We speculate that when the inflammatory process is sufficient in duration or severity, changes in morphologic characteristics of the airways will develop, leading to impairment of lung function, such as has been proposed in humans with asthma.…”
Section: Discussionsupporting
confidence: 92%
“…The extent of pulmonary neutrophilia observed in these previous studies varied, being either diffuse or localised to the lavaged segment. In contrast to these findings, Derksen et al (1987) demonstrated that three repeated BALs, performed in different segments within a 29-h period, did not significantly affect BALF cytology of 3 ponies.…”
Section: Discussioncontrasting
confidence: 80%
“…Peripheral eosinophilia and eosinophilic respiratory secretions associated with positive intradermal and serum precipitin tests to Saccharopolyspora rectivirgula (formerly Micropolyspora faeni ) have been reported 13 . However, experimental aerosol challenge of sensitized ponies with S. rectivirgula induced increased neutrophils but not eosinophils in respiratory secretions, and no clinically relevant changes in peripheral eosinophil count, 14 perhaps supporting the role of S. rectivirgula in recurrent airway obstruction but not in eosinophilic pulmonary disease. Other allergens, however, could possibly contribute to the development of eosinophilic disease in horses.…”
Section: Discussionmentioning
confidence: 88%